How to Be Free: An Ancient Guide to the Stoic Life - Epictetus (Princeton: Princeton University Press, 2018)
"Born a slave, the Roman Stoic philosopher Epictetus (c. 55-135 AD) taught that mental freedom is supreme, since it can liberate one anywhere, even in a prison ... Freedom, for Epictetus, is not a human right or a political prerogative but a psychological and ethical achievement, a gift that we alone can bestow on ourselves ... How to Be Free features splendid new translations and the original Greek on facing pages, a compelling introduction that sets Epictetus in context and describes the importance of Stoic freedom today, and an invaluable glossary of key words and concepts. The result is an unmatched introduction to this powerful method of managing emotions and handling life's situations, from the most ordinary to the most demanding."--Provided by the publisher.
Keywords: Epictetus--Early to 1800.; Epictetus--Manual.--Selections.; Stoics